2020
DOI: 10.3390/ijerph17165679
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity on Prescription in Routine Health Care: 1-Year Follow-Up of Patients with and without Counsellor Support

Abstract: The effectiveness of counsellor support in addition to physical activity on prescription (PAP) from health care professionals has rarely been evaluated. This observational follow-up study investigated differences in physical activity levels and health-related quality of life (HRQoL) one year after PAP regarding patients’ use of counsellor support in addition to PAP in routine care. The study was conducted in a Swedish health care region in which all patients receiving PAP from health care professionals were of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Studies suggest the importance of social support for patients receiving PAP [ 29 31 ]. Previous studies by the researchers behind the present study have indicated that counselor support in association with delivery of PAP is beneficial for increased physical activity [ 28 , 32 ]. However, the association between counselor support and other factors has not been elucidated.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Studies suggest the importance of social support for patients receiving PAP [ 29 31 ]. Previous studies by the researchers behind the present study have indicated that counselor support in association with delivery of PAP is beneficial for increased physical activity [ 28 , 32 ]. However, the association between counselor support and other factors has not been elucidated.…”
Section: Introductionmentioning
confidence: 82%
“…The baseline responders were sent a follow-up questionnaire after 1 year. The recruitment process has been described previously by the authors of this study [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The studies collectively investigated 36 PARS models, and seven schemes were researched by multiple studies. The Swedish Physical Activity on Prescription (PAP) model was investigated the most [ 35 38 , 40 44 , 58 , 70 – 72 , 89 91 ], with some studies examining schemes with the standard core components of this model [ 35 38 , 41 , 58 , 72 ] and others focusing on enhanced variations [ 40 , 42 , 43 , 70 , 71 ]. The second most investigated model was the Green Prescription (GRx), originating from New Zealand, including the standard scheme [ 48 , 62 , 92 ] and variations [ 47 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies did not report added benefits for an enhanced intervention over standard provisions [ 42 45 , 73 , 85 ]. However, two trials [ 64 , 65 ] and one observational study [ 70 ] reported that more intensive PARS offer added benefits for participants, and one study reported inconsistent results [ 55 ]. Observational and pre-post studies consistently reported an increase in PA levels for PARS participants [ 35 , 37 , 68 , 71 , 72 , 75 , 76 , 78 80 , 84 , 86 ], with the exception of one study [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 48% adherence rate at 5 years obviously increased the risk of selection bias. However, similar PAP studies with shorter follow-up times have shown dropout rates of between 30–38% at 6–12 months of follow-up [ 57 59 ], and 41–48% at 2 years of follow-up [ 60 , 61 ]. Additionally, the large LOOK-ahead study reported very low compliance even after only 2 years of the 10-year follow-up, as indicated by the fitness values and metabolic risk factors returning to normal [ 24 ].…”
Section: Discussionmentioning
confidence: 96%